Peran Orang Tua Dalam Mendukung Perkembangan Potensi Anak Usia Dini - Azzahra, Anantha; Nihwan; Rismayanti (Anakta : Jurnal Pendidikan Islam Anak Usia Dini, 2024)
Children are a gift from God as a mandate to carry out their duties in the world, such as being human beings with good character and being useful to others. Likewise, parents are the first foundation for their children to teach all education. The aim of the research is to find out the importance of parents in understanding potential development, so they can follow their children's interests and talents. Talent in children usually arises from hobbies that they like, if parents support the development of the child's potential. This research method uses a qualitative descriptive approach which produces descriptions in the form of written or spoken words from the sources studied, using data collection techniques such as interviews, observation, data analysis techniques and research objects. The results obtained by researchers show that the role of parents in developing the potential of early childhood does not look good, because most parents there do not know the science of parenting and several external and internal factors. The role of parents really helps develop children's potential in cultivating interests and talents. Parents are expected to play an active role and always be a support system in their child's growth and development.